Modern state of maritime export transport service of ukraine (Transport systems and technologies, 2019)
The geographical location of Ukraine, which has access to the Black and Azov Seas, gives wide opportunities for using sea routes to provide transportation services for export cargo flows. Some goods of Ukrainian export are almost completely handled in sea ports and respectively are shipped to the countries of their import by the maritime fleet. The article presents the analytical review on the participation of domestic seaports and merchant fleets in providing the Ukrainian export in the dynamics over the past five years. The materials for the present study were the relevant statistics from the Ukrainian Sea Ports Authority and the State Statistics Service of Ukraine. Ukraine's port capacities are quite significant and take an active part in transporting goods of Ukrainian exports, handling major domestic export goods in large volumes. The structure of cargoes handled in Ukrainian ports is predominantly raw material and to a large extent duplicates the existing structure of Ukrainian export. These are mostly ferrous metals, grain products, ores and building materials. The article presents indices that characterize the volumes and structure of export cargo flows in domestic ports. On the contrary, the merchant fleet, which could be used for the relevant transportation, is actually absent in Ukraine, which explains its negligible participation in the carriages of export goods.
Keywords: sea ports, merchant fleet, carriages of export cargoes by sea